Ageing as a mindset: a study protocol to rejuvenate older adults with a counterclockwise psychological intervention. Issue 7 (9th July 2019) - Pagnini, Francesco; Cavalera, Cesare; Volpato, Eleonora; Comazzi, Benedetta; Vailati Riboni, Francesco; Valota, Chiara; Bercovitz, Katherine; Molinari, Enrico; Banfi, Paolo; Phillips, Deborah; Langer, Ellen
Abstract : Introduction: Although ageing is generally perceived as a biologically determined process, the literature increasingly points to the importance of psychological factors in the ageing process, specifically age-related stereotypes or cognitive mindsets. Such stereotypes reflect self-perceptions and others' perceptions about the ageing process and can have a strong influence on health and life satisfaction, specifically through self-fulfilling prophecy mechanisms. This study aimed to investigate whether changes in mindsets can change the ageing process. Methods and analysis: This study replicates in large part the original 1979 'Counterclockwise' experiment by Ellen Langer and will involve a group of older adults (aged 75+) taking part of a 1-week retreat outside of Milan, Italy. Participants will be instructed and helped to relive their younger selves, acting as i f they are living in the year 1989. The week-long residential programme is designed to prime this perception by incorporating a completely retrofitted physical environment, as well as providing opportunities to engage in social activities that would have been common in the late 1980s. This 'counterclockwise' intervention will be tested as a randomised control trial comprised of the experimental ('counterclockwise') group, an active control group (same activities, no time manipulation) and a no-treatment group. Ninety participants will be randomly allocated to one of these three conditions. Every participant will be assessed for medical, cognitive, psychological and age appearance at four time points: at the time of recruitment, after the intervention (ie, after a week for the no-treatment group) and again after 6 and 12 months. Ethics and dissemination: The study has been approved by the Ethics Committees of the Department of Psychology of Università Cattolica del Sacro Cuore and Don Gnocchi Foundation. Results will be disseminated through peer-reviewed journals, scientific meetings and direct presentation to the general population. Trial registration number: NCT03552042 ; Pre-results.